Development of 2D Animation Learning Mediafor Animal Life Cycle Material - Rizkita Ayu Mutiarani; I Ketut Wiguna; I Putu Susila Handika (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
Learning media plays a strategic role in supporting the success of the teaching and learning process. In education, animation is widely used as a modern instructional medium, particularly to represent learning materials that are difficult to explain verbally. This output was developed as an alternative instructional medium for science learning, especially to explain process-oriented concepts that may be difficult for students to understand when delivered only through verbal explanation or static images. The product was created in the form of a 2D animated video in MP4 format, integrating illustrations, frame-by-frame animation, text, voice-over, sound effects, and background music. The production process employed Adobe Photoshop 2021 for visual asset creation and animation, and Adobe Premiere Pro 2020 for post-production. The material presented in the media covers animal life cycles without metamorphosis, represented by chickens and fish, as well as animal life cycles with metamorphosis, represented by frogs, butterflies, and cockroaches. The media consists of 20 scenes arranged narratively through two characters, Kirana and Leoni, who serve as learning guides. The evaluation results showed that the media received highly positive responses from 33 fifth-grade students, with an average score of 88.2%. The measurement of students’ conceptual understanding through pre-test and post-test results produced an average N-Gain score of 0.89, which falls into the high category. Therefore, this 2D animation learning media output is considered feasible to be used as a supporting instructional medium for teachers in delivering animal life cycle material in elementary schools.